Assesment of the efficiency of conchal auricular cartilage graft in management of orbital floor fracture - اسعد منذر; ديب محمد (Latakia University Journal -Medical Sciences Series, 2022)
This study aimed to evaluate the effectiveness of cartilage graft taken from the ear in repairing fractures of the orbital base in cases of minimal bon damage 2*2 cm. The research sample consisted of 15 cases submitted to the Department of Oral and Maxillofacial Surgery at Tishreen University Hospital, with orbital floor fractures. The time factor for surgery after trauma was taken into account. The clinical observation contained studying of diplopia through15 days, month, and 3months after the surgery . The results showed that there were statistically significant differences during the follow-up period after the surgical operation, where the eye movements returned completely after three months, as well as the normal positioning of the eyeball returned to the affected side compared to the eyeball of the healthy side, as well as the decline of diplopia during the follow-up period. The use of conchal auricular cartilage graft in the repair of orbital floor fractur led to an improvement in the functional aspect of the eyeball and the return of the functional and aesthetic aspect to this important part of the face.